TGV for diffusion tensors: A comparison of fidelity functions - Valkonen, Tuomo; Bredies, Kristian; Knoll, Florian (Journal of Inverse and Ill-posed Problems, 2013)
We study the total generalised variation regularisation of symmetric tensor fields from medical applications, namely diffusion tensor regularisation. We study the effect of the pointwise positivity constraint on the tensor field, as well as the difference between direct denoising of the tensor field first solved from the Stejskal-Tanner equation, as was done in our earlier work, and of incorporating this equation into the fidelity function. Our results indicate that the latter novel approach provides improved computational results. © de Gruyter 2013.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Diffusion tensor imaging; Medical imaging; Regularisation; Total deformation; Total generalised variation